Coping with the diagnosis and hospitalization of a child with childhood cancer - Tainan de Cerqueira Nóia; Ricardo Souza Evangelista Sant'Ana; Ana Dulce Santana dos Santos; Sheila de Carvalho Oliveira; Sylvia Maria Cardoso Bastos Veras; Luís Carlos Lopes-Júnior (Universidad de Antioquia, 2015)
Objective.Find out how family members cope with hospitalization due to the diagnosis of childhood cancer. Methodology. This is a descriptive-exploratory design study with qualitative data analyses, undertaken in the Support Center for Childhood Cancer in Salvador, Bahia, Brazil. 10 members of the families of children with cancer underwent a semi-structured interview as a resource to collect empirical data. Data were submitted to thematic content analysis. Two categories emerged: "family coping with diagnosis" and "family coping with hospitalization." Results. It was observed that family members suffer deeply and cope with the diagnosis of cancer in different manners. In addition, psychological stress has a cumulative impact on long periods of hospitalization and occurs in the presence of sadness, anxiety, suffering due to the invasive procedures the children are submitted to, fear and uncertainties related to prognosis. Conclusion. The diagnosis of cancer and hospitalization process causes severe impact on family dynamics. A competent nurse must be aware and sensitive to minimize this suffering by listening carefully and providing humanized and comprehensive care to children and their families.